Enhanced Biogas Production From Anaerobic Co-digestion of Lignocellulosic Biomass and Poultry Feces Using Source Separated Human Urine as Buffering Agent - Eduok, Samuel; John, Ofonime; Ita, Basil; Inyang, Edidiong; Coulon, Frédéric (Frontiers in Environmental Science, 2018)
Effect of source separated human urine as buffering agent compared to sodium bicarbonate and water in anaerobic co-digestion of lignocellulosic biomass and poultry faeces was evaluated in laboratory scale reactor for 180 days at 37 ± 2 ⁰C. Mean biogas volume ranged from 37 ± 8 to 101 ± 18 mL gVS⁻¹ in the urine buffered reactors which was 1 to 5 times higher than the bicarbonate and water buffered reactors and the difference was significant at p = 0.05. Total volatile fatty acids (VFA) concentration ranged between 396 and 1400 mg L⁻¹ with a pH of 6.9 ± 0.3 and 7.8 ± 0.1, respectively. In contrast, VFA concentration ranged between 386 and 3109 mg L⁻¹ (pH 7.6 ± 0.2 and 4.8 ± 0.4) in sodium bicarbonate buffered digestate and control (water) respectively. The result indicates buffering capacity of urine on anaerobic co-digestion with positive effect on biogas production. The Archaeal isoprenoids included markers of aceticlastic and hydrogenotrophic methanogens with a relative abundance that ranged from between 0.71 to 18, 3 to 55, and 2 to 59 µg g⁻¹ dry matter in the water (control), bicarbonate and urine buffered digestate, respectively. The Archaeal abundance was 1.12 and 6 times higher in the combined female/male urine than the bicarbonate buffered digestate and the control, and the difference was significant at p = 0.05. Overall, this study demonstrates that human urine with no pharmaceutical loadings as a wetting and buffering agent is a promising option for anaerobic co-digestion with competitive edge over sodium bicarbonate on lignocellulosic biomass saccharification for enhanced biogas production.